The crimson petal and the white - Faber, Michel, ....- (Edinburgh : Canongate, 2003)
Sugar, 19, prostitute in Victorian London, yearns for a better life. From brutal brothel-keeper Mrs Castaway, she ascends in society. Affections of self-involved perfume magnate William Rackham soon smells like love. Her social rise attracts preening socialites, drunken journalists, untrustworthy servants, vile guttersnipes, and whores of all kinds.
Keywords: Fiction